The effects of a semi‐rigid ankle brace on a simulated isolated subtalar joint instability. Issue 12 (22nd August 2013) - Choisne, Julie; Hoch, Matthew C.; Bawab, Sebastian; Alexander, Ian; Ringleb, Stacie I.
Abstract: Subtalar joint instability is hypothesized to occur after injuries to the calcaneofibular ligament (CFL) in isolation or in combination with the cervical and the talocalcaneal interosseous ligaments. A common treatment for hindfoot instability is the application of an ankle brace. However, the ability of an ankle brace to promote subtalar joint stability is not well established. We assessed the kinematics of the subtalar joint, ankle, and hindfoot in the presence of isolated subtalar instability, investigated the effect of bracing in a CFL deficient foot and with a total rupture of the intrinsic ligaments, and evaluated how maximum inversion range of motion is affected by the position of the ankle in the sagittal plane. Kinematics from nine cadaveric feet were collected with the foot placed in neutral, dorsiflexion, and plantar flexion. Motion was applied with and without a brace on an intact foot and after sequentially sectioning the CFL and the intrinsic ligaments. Isolated CFL sectioning increased ankle joint inversion, while sectioning the CFL and intrinsic ligaments affected subtalar joint stability. The brace limited inversion at the subtalar and ankle joints. Additionally, examining the foot in dorsiflexion reduced ankle and subtalar joint motion. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. Published by Wiley Periodicals, Inc. J Orthop Res 31:1869–1875, 2013